Review of the First International Conference «World Medicine in Everyday Practice» - I. V. Kovaleva (Лечащий Врач)
From 3 to 4 December 2020, the First International Conference «World Medicine in Everyday Practice», organized by the pharmaceutical and biotechnology company Adamed Pharma, was held online. The conference was attended by more than 6,5 thousand from 9 countries of the world, the focus of which was on topical issues of management in the era of COVID-19 of patients with cardiovascular, endocrine and surgical pathology, as well as bronchial asthma, COPD, severe colitis caused by Clostridioides difficile, disorders sleep, depression and other illnesses. Leading experts from various fields of medicine delivered lectures on topics that are significant for doctors around the world, demonstrated a picture of a pandemic in the future of various regions of the planet, assessed the current state of knowledge about COVID-19 and the clinical consequences of a new coronavirus infection in medical practice. The participants of the event expressed their intention to continue the discussion of topical problems of modern medicine in a series of international meetings initiated by Adamed Pharma, which provided doctors from different countries with a unique opportunity to exchange views and share best practices in the treatment of patients with various diseases against the background of COVID-19.